PARTISIPASI MASYARAKAT DALAM PENYUSUNAN RENCANA KERJA PEMERINTAH DESA (Studi Kasus Desa Tingkohubu Kecamatan Suwawa Kabupaten Bone Bolango) - Joice Machmud; Harijono Imbran; Rulyanti Gaib (Akademika : Jurnal Ilmiah Media Publikasi Ilmu Pengetahuan dan Teknologi, 2025)
This study aims to determine community participation in the case study vi lage government work plan in Tinngkohubu Vi lage, Suwawa District, Bone Bolango Regency. This study uses a qualitative approach and uses an interview instrument. The results of the study conclude that community participation in the preparation of vi lage government work plans is sti l not visible, although the vi lage government rea ly hopes that community participation can at least attend meetings or meetings held by the government so that they can provide thoughts and suggestions. But in reality this is very difficult to achieve. The community is more focused on accepting the development programs implemented by the vilage government.